2017
DOI: 10.1080/08870446.2017.1293270
|View full text |Cite
|
Sign up to set email alerts
|

“Why me?” – women’s use of spiritual causal attributions in making sense of breast cancer

Abstract: Although positive spiritual attributions may help women maintain an attitude of hope and acceptance in the face of cancer, results indicate that the effects of negative spiritual attribution can play a significant role in undermining their well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(60 citation statements)
references
References 49 publications
0
55
0
5
Order By: Relevance
“…[ 12 ] Religiosity is an essential component of palliative care that has attracted increasing interest in recent years among cancer patients, especially those with breast cancer. [ 13 14 ] Religiosity is an expression of spirituality and is defined as a set of beliefs and practices associated with a particular religious tradition or denomination. [ 15 ] Associations between religiosity and QoL in patients with breast cancer have been discussed in different cultures, with conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…[ 12 ] Religiosity is an essential component of palliative care that has attracted increasing interest in recent years among cancer patients, especially those with breast cancer. [ 13 14 ] Religiosity is an expression of spirituality and is defined as a set of beliefs and practices associated with a particular religious tradition or denomination. [ 15 ] Associations between religiosity and QoL in patients with breast cancer have been discussed in different cultures, with conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosis of breast cancer disturbs the functioning of many, if not all, women in almost every sphere of life [4,5]. The psychological sphere is one of the most important because, apart from the ill person, also people who are the closest experience various types of negative emotions, such as fear, anger, the feeling of threat, helplessness and uncertainty [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Another important factor is spirituality, since it becomes important as it begins the search for hope and quality of life at the end of life. It is important to say that the spiritual role can be both positive (the event is due to the love or will of god) and negative (the event is due to the wrath of god) that the patient attributes to having cancer [5], however studies have shown that patients consider that the accompaniment in spiritual and religious issues by the doctor can be something that benefits them [6]. Although this point is not a frequent practice in clinical practice and is difficult for health personnel to address, it is a measure of care that favors the trust, tranquility and hope of the patient, in the midst of the adversity of cancer [6].…”
Section: Development and Discussionmentioning
confidence: 99%